Scattering light by light at 750 GeV at the LHC - Fichet, S. [UNESP]; Von Gersdorff, G. [UNESP]; Royon, C. (American Physical Society (APS), 2016)
We consider the possibility that the diphoton excess at 750 GeV is caused by a new scalar resonance produced in photon fusion. This scenario is parametrized by only one relevant effective couplings and is thus minimal. We show that this setup can reproduce both the production rate and width of the resonance, and is not in conflict with the 8 TeV limits on the diphoton cross section. The scenario also predicts event rates for WW, ZZ, Zγ final states. We suggest for one to perform precision measurements by studying light-by-light scattering with intact protons detected in forward detectors. We construct a simple model that shows that the required couplings can be achieved with new vectorlike, uncolored fermions (with a strong Yukawa coupling to the resonance) which may also account for the required width.